The Effects of Domestic Demand and Export on Economic Growth of North Sumatra - Jongkers Tampubolon; Aaron Loh (Jurnal Ekonomi dan Studi Pembangunan, 2020)
The objective of this study is to investigate the roles of domestic demand and export in the economic growth of North Sumatra, Indonesia. Specifically, this study examined: (i) the effect of domestic demand and export on economic growth, (ii) the effect of domestic demand components (i.e., private consumption, government consumption, and investment) on economic growth, and (iii) causal relationships between domestic demand, export, and economic growth. Using the autoregressive distributed lag (ARDL) bound test for cointegration, the study revealed thatNorth Sumatra’s economic growth is not driven by export. Export and economic growth do not affect each other, whereas domestic demand and economic growth influence each other dynamically. In the short-run, private consumption and investment have positive and significant effects on economic growth. However, in the long-run, only private consumption has a significant effect. ARDL Granger causality analysis showed that in the short-run, only private consumption has a causal relationship with economic growth. The absence of the causal relationships between both investment and government expenditure and economic growth indicates that the export sector, which is growing rapidly in both monetary terms and its shares in the regional gross domestic products (GDP), is isolated from the regional economic activities.